Will Narcissistic People Choose Narcissistic Leaders Too? The Effect of Narcissism on Leadership Perceptions - Hidayaturahman, Ichwan Febri; Nuzulia, Siti (Journal of Educational, Health and Community Psychology, 2025)
Narcissism refers to a condition in which individuals excessively love themselves, whereas leadership is a process of influencing others to achieve shared goals within a group. This study aims to examine the extent to which narcissism influences perceptions of leadership and the decision to select a leader. It also explores the impact of personality similarity on leadership perceptions and leader selection decisions. The findings reveal differences in leadership perceptions between candidates with high and low levels of narcissism. Leaders with high narcissism are perceived more positively and are more likely to be recommended for leadership positions compared to those with low narcissism. However, the similarity in narcissism between leaders and candidates does not influence the decision to choose a leader. This research addresses the gap in the study of the relationship between narcissism and leadership perceptions in Indonesia, where narcissism is often viewed negatively in the context of leadership. The findings indicate that personality similarity (narcissism) between voters and leadership candidates does not significantly affect voter perceptions or recommendations. Practically, this study demonstrates that narcissism can be a factor in selecting a leader, although personality similarity does not necessarily determine voting decisions.